The heroic leadership imperative : how leaders inspire and mobilize change - Allison, Scott T.; Goethals, George R. (Bingley, U.K. : Emerald Publishing Limited, 2020)
In The Heroic Leadership Imperative, Scott T. Allison and George R. Goethals identify leaders who have succeeded in meeting all three categories of needs and they discuss such leaders' appeal by way of a unique integration classic and contemporary psychology relevant to understanding all facets of heroism and heroic leadership.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Leadership; Business & Economics -- Leadership; Management: leadership & motivation